Engineering Acetogenic Bacteria for Efficient One-Carbon Utilization - Lee, Hyeonsik; Bae, Jiyun; Jin, Sangrak; Kang, Seulgi; Cho, Byung-Kwan (Frontiers in Microbiology, 2022)
C1 gases, including carbon dioxide (CO2) and carbon monoxide (CO), are major contributors to climate crisis. Numerous studies have been conducted to fix and recycle C1 gases in order to solve this problem. Among them, the use of microorganisms as biocatalysts to convert C1 gases to value-added chemicals is a promising solution. Acetogenic bacteria (acetogens) have received attention as high-potential biocatalysts owing to their conserved Wood–Ljungdahl (WL) pathway, which fixes not only CO2 but also CO. Although some metabolites have been produced via C1 gas fermentation on an industrial scale, the conversion of C1 gases to produce various biochemicals by engineering acetogens has been limited. The energy limitation of acetogens is one of the challenges to overcome, as their metabolism operates at a thermodynamic limit, and the low solubility of gaseous substrates results in a limited supply of cellular energy. This review provides strategies for developing efficient platform strains for C1 gas conversion, focusing on engineering the WL pathway. Supplying liquid C1 substrates, which can be obtained from CO2, or electricity is introduced as a strategy to overcome the energy limitation. Future prospective approaches on engineering acetogens based on systems and synthetic biology approaches are also discussed.